Vietnam in the global economy : the dynamics of integration, decentralization, and contested politics - Jandl, Thomas, 1965- (Lexington Books, 2013)
"Describes in a game-theoretical approach how the development success story Vietnam managed to keep rent seeking in check sufficiently to attract record numbers of foreign investors and exhibit strong economic growth in the early stages of its economic reforms. It concludes that pluralistic contestation among societal interests under conditions of factor mobility can lead to the same benefits that are generally associated with liberal democracy--commitment to limited government through checks and balances"--